Effect of aerial exposure on the antioxidant status in the subantarctic stone crab Paralomis granulosa (Decapoda: Anomura) - Romero, Maria Carolina; Ansaldo, Martin; Lovrich, Gustavo Alejandro (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology)
In Tierra del Fuego (Southern South America), the stone or false king crab, Paralomis granulosa represents one of the most important crabfisheries. After capture, animals are kept in baskets and exposed to dryness for several hours, when the water flow through the gills is interrupted.As a consequence a concomitant increase of reactive oxygen species begins, triggering oxidative stress. The aim of this study was to determineoxidative stress and antioxidant enzyme activities due to air exposure in different tissues of P. granulosa. Fifty crabs (carapace length N82 mm)were captured in Beagle Channel (54° 50′S, 68° 20′W) during winter 2004. Five groups of 10 crabs each were exposed to dryness at 6°C for 0, 3,6, 12 or 24 h, respectively. Activity of superoxide dismutase (SOD), catalase (CAT), glutathione S transferase (GST) protein and lipid oxidationwere measured in gills, muscle, hepatopancreas and haemolymph samples. Almost all analyzed tissues showed antioxidant enzymes activity,which varied with time of air exposure. The maximum enzyme activity was measured after 6 h of air exposure. Protein oxidation levels variedsignificantly in gills. Lipid peroxidation levels increased significantly in muscle and hepatopancreas. The critical time of air exposure probablyoccurs at 6 h. Thereafter animals were unable to induce the synthesis of antioxidant enzymes or proteins. This should be taken into account tominimize the stress generated by the commercial capture process. Fil: Romero, Maria Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Ansaldo, Martin. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Lovrich, Gustavo Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina